Preparation method and application of coordination polymer-based electrocatalyst
Through the preparation of bistriazole-type metal organic frame material Ag/Cu/Co-L, the synergistic effect of polymetals is used to solve the problems of high cost of precious metal catalysts and insufficient activity stability of a single transition metal compound, and efficient electrocatalysis is achieved Water cracking, low voltage full hydrolysis and excellent catalytic properties.
Patent Information
- Application Number
- CN202411376159.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
AI Technical Summary
The high cost and low reserves of precious metal catalysts in traditional electrocatalytic systems limit the sustainable development of electrocatalytic water cracking, and a single transition metal compound is difficult to have high catalytic activity and stability, especially in the OER semi-reaction of four electrons to move. Inefficient learning.
Using bistriazole-type metal organic frame material Ag/Cu/Co-L, the coordinated polymer is prepared by hydrothermal method, using Cu2+, Co2+ and Ag+ as nodes, combining H2BBTA ligands to achieve high entropy synergistic effect of polymetals , regulates the electronic structure and active sites, and improves catalytic performance.
The total decomposition of water is achieved under low voltage conditions, the overpotentials of OER and HER are lower than those of commercial catalysts, and the Tafel slope is excellent, showing efficient electrocatalytic performance and stability, meeting the energy storage and conversion needs of clean energy.
Smart Images

Figure CN119264448A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation method of a coordination polymer-based electrocatalyst and application thereof, belonging to the technical field of electrocatalytic materials for water splitting. Background Art
[0002] Energy is a fundamental need for human development. However, the gradual depletion of traditional fossil fuels and the resulting environmental pollution pose significant obstacles to sustainable development. Therefore, the development of efficient and environmentally friendly renewable energy sources and related technologies is urgently needed. Hydrogen energy offers advantages such as high energy density, low / zero carbon emissions, and storability. Electrocatalytic water splitting for oxygen / hydrogen evolution reactions (OER / HER) is a promising renewable resource storage and conversion technology. However, the efficiency of the water splitting process, particularly the OER half-reaction for oxygen evolution, is significantly limited by sluggish multi-electron transfer kinetics. Currently, commercial electrolysis systems mostly use Pt-based catalysts for the HER reaction and Ir, Ru, and their oxides for the OER reaction. The low reserves and high cost of noble metals limit their large-scale commercial application in electrocatalytic materials. Therefore, the development of relatively inexpensive and abundant transition metal-based electrocatalysts is urgently needed. However, single abundant transition metal compounds struggle to achieve both high catalytic activity and stability in electrocatalytic water splitting.
[0003] In recent years, high-entropy alloy-type materials with multi-metal alloying characteristics can regulate the local electronic structure of catalysts, which is beneficial for the adsorption and activation of substrates. The excellent performance of high-entropy alloys in electrocatalytic applications has attracted widespread attention and provided inspiration for us to break through the limitations of single metal compounds and develop multi-metal materials for electrocatalytic water splitting. By utilizing the synergistic effect of multiple abundant transition metals similar to "high-entropy alloys", the advantages of each metal in water splitting are combined to achieve catalytic performance far exceeding that of single metals. However, the structure of electrocatalysts is easily affected by allosteric effects under electrochemical water splitting conditions, resulting in the weakening of atomic-level contacts and functional synergy between multi-metal centers. Therefore, it is crucial to achieve highly uniform dispersion of multiple metals in electrocatalytic materials and maintain the stability of the framework structure and the high dispersion characteristics of multi-metals during the electrocatalytic process.
[0004] Metal-organic frameworks (MOFs), crystalline inorganic-organic composites with tailorable structures and tunable functions and properties, have shown particular potential in electrocatalysis. The incorporation of two or even multiple metal ions into the metal cluster nodes of MOFs can manipulate the coordination environment, alter the electronic structure of the active sites, and promote synergistic interactions between active intermediates. Ligands with triazole-coordinated end groups exhibit soft edge base pairs and multidentate structures. According to the hard-soft-base theory, the coordination of soft-base triazole ligands with soft-acid transition metals exhibits short metal-ligand distances and excellent stability. "High-entropy" MOFs, assembled from bistriazole ligands and a variety of abundant metal ions, provide a uniform coordination environment for different metal reaction centers, modulate the synergistic electronic effects of multiple metal ions, and withstand the alkaline aqueous reaction conditions of electrocatalytic water splitting, effectively maintaining isomorphism and monodispersity of the metal centers during electrocatalysis.
[0005] This patent designs a bistriazole-type metal-organic framework (named Ag / Cu / Co-L) containing abundant transition metals Cu and Co and inexpensive precious metal Ag. Ag / Cu / Co-L has advantages such as abundant active sites, multi-metal regulated electronic structure and interfacial synergistic effects, and exhibits excellent activity in water splitting reactions. Ag / Cu / Co-L is particularly capable of overcoming the four-electron transfer kinetics limitation in the oxygen evolution half-reaction (OER) and exhibits excellent performance at 10 mA∙cm -2 At a current density of 1.5 GHz, the overpotential is 208 mV and the Tafel slope is as low as 35.89 mV∙dec. -1 ; at 10 mA∙cm -2 Under the conditions of Ag / Cu / Co-L, the overpotential of HER hydrogen evolution reaction is 209 mV, and the Tafel slope is 61.20 mV∙dec. -1 Ag / Cu / Co-L was loaded on carbon paper (CP) substrate as cathode and the charge transfer rate was 10 mA∙cm -2 Complete water splitting was achieved at a low voltage of 1.58 V, a voltage lower than that of commercial RuO2 (1.65 V) and Pt / C (1.68 V). This excellent result is comparable to many recently reported catalysts. This suggests that trimetallic bistriazole metal-organic frameworks (MOFs) are promising candidates for clean energy storage and conversion. Summary of the Invention
[0006] To overcome the problems of existing technologies, the present invention provides a method for preparing and applying a coordination polymer-based electrocatalyst. As electrode materials for complete hydrolysis, coordination polymer-based electrocatalysts exhibit excellent electrochemical performance in electrocatalytic water splitting, providing a powerful approach for designing efficient electrode materials for energy conversion and environmental remediation.
[0007] In order to achieve the above-mentioned purpose of the invention and solve the problems existing in the prior art, the technical solution adopted by the present invention is: a method for preparing a coordination polymer-based electrocatalyst, wherein L is an organic ligand, Cu in the transition metal salt TM 2+ 、Co 2+ and Ag + Single-metal coordination polymers Co-L, Cu-L, Ag-L, bimetallic coordination polymers Cu / Co-L, Ag / Co-L, Ag / Cu-L, and trimetallic coordination polymer Ag / Cu / Co-L were prepared as nodes by a hydrothermal method. The synthesis routes are as follows:
[0008] For single metal: L+TM→Co-L, L+TM→Cu-L, L+TM→Ag-L;
[0009] For bimetallic: L+TM→Cu / Co-L, L+TM→Ag / Co-L, L+TM→Ag / Cu-L;
[0010] For trimetallic: L+TM→Ag / Cu / Co-L;
[0011] The organic ligand L is selected from {H2BBTA=1,5-dihydrobenzo[1,2-d:4,5-d']bis[1,2,3]triazole},
[0012] The molecular formula is C6H4N6, and it has the following molecular structure (A):
[0013]
[0014] The transition metal salt TM is selected from silver chloride, cobalt chloride hexahydrate or copper chloride dihydrate;
[0015] The preparation method includes the preparation of single-metal coordination polymers Co-L, Cu-L, and Ag-L, the preparation of bimetallic coordination polymers Cu / Co-L, Ag / Co-L, and Ag / Cu-L, and the preparation of trimetallic coordination polymer Ag / Cu / Co-L:
[0016] (1) Preparation of single metal coordination polymers Co-L, Cu-L, and Ag-L, including the following steps:
[0017] Step 1. Add 8-10 mg of ligand {H2BBTA = 1,5-dihydrobenzo[1,2-d:4,5-d']bis[1,2,3]triazole}, 9-12 mg of silver chloride, 13-16 mg of cobalt chloride hexahydrate or 10-13 mg of copper chloride dihydrate to 1-3 ml of acetonitrile, 1-3 ml of N,N-dimethylformamide, and 0.25-0.5 ml of hydrochloric acid, and stir evenly for 25-35 minutes;
[0018] Step 2: Add the mixed solution prepared in step 1 to a 25-50 mL stainless steel autoclave lined with polytetrafluoroethylene and seal it. Then, store it in an oven at 30-70°C for 48-72 hours. After slowly cooling to room temperature, filter the crystals, wash them with methanol 1-3 times, and finally dry them in a vacuum drying oven at 60-80°C for 6-12 hours.
[0019] (2) Preparation of bimetallic coordination polymers Cu / Co-L, Ag / Co-L, and Ag / Cu-L, including the following steps:
[0020] Step 1. Add 8-10 mg of ligand {H2BBTA = 1,5-dihydrobenzo[1,2-d:4,5-d']bis[1,2,3]triazole}, 9-12 mg of silver chloride, 13-16 mg of cobalt chloride hexahydrate, and 10-13 mg of copper chloride dihydrate in a molar ratio of Co / Cu, Ag / Co, and Ag / Cu of 1:1 to 1-3 ml of acetonitrile, 1-3 ml of N,N-dimethylformamide, and 0.25-0.5 ml of hydrochloric acid, and stir evenly for 25-35 minutes;
[0021] Step 2: Place the mixed solution prepared in step 1 into a 25-50 mL stainless steel autoclave lined with polytetrafluoroethylene and seal it. Then, store it in an oven at 30-70°C for 48-72 hours. After slowly cooling to room temperature, wash it with methanol 1-3 times, and finally dry it in a vacuum drying oven at 60-80°C for 6-12 hours.
[0022] (3) Preparation of trimetallic coordination polymer Ag / Cu / Co−L, including the following steps:
[0023] Step 1. Add 8-10 mg of ligand {H2BBTA = 1,5-dihydrobenzo[1,2-d:4,5-d']bis[1,2,3]triazole}, 9-12 mg of silver chloride, 13-16 mg of cobalt chloride hexahydrate, and 10-13 mg of copper chloride dihydrate at a molar ratio of Ag / Cu / Co (0.5-3):1:1 to 1-3 ml of acetonitrile, 1-3 ml of N,N-dimethylformamide, and 0.25-5 ml of hydrochloric acid, and stir evenly for 25-35 minutes;
[0024] Step 2: Place the mixed solution prepared in step 1 into a 25-50 mL stainless steel autoclave lined with polytetrafluoroethylene and seal it. Then, store it in an oven at 30-70°C for 48-72 hours. After slowly cooling to room temperature, wash it with methanol 1-3 times, and finally dry it in a vacuum drying oven at 60-80°C for 6-12 hours.
[0025] The invention relates to an application of the coordination polymer-based electrocatalyst prepared by the method in electrocatalytic water decomposition.
[0026] The beneficial effects of the present invention are: a method for preparing a coordination polymer-based electrocatalyst, wherein L is an organic ligand, Cu in a transition metal salt TM 2+ 、Co 2+ and Ag + Single-metal coordination polymers Co-L, Cu-L, Ag-L, bimetallic coordination polymers Cu / Co-L, Ag / Co-L, Ag / Cu-L, and trimetallic coordination polymer Ag / Cu / Co-L were prepared as nodes by a hydrothermal method. The synthesis routes are as follows:
[0027] For single metal: L+TM→Co-L or L+TM→Cu-L or L+TM→Ag-L;
[0028] For bimetallic: L+TM→Cu / Co-L, L+TM→Ag / Co-L, L+TM→Ag / Cu-L;
[0029] For trimetallic: L+TM→Ag / Cu / Co-L;
[0030] The Ag / Cu / Co-L prepared by the method of the present invention has excellent electrochemical performance. -2 Ag / Cu / Co-L has a low overpotential. In 1 M KOH solution, the overpotentials of OER and HER are 209 mV and 208 mV, respectively, and it also has a high Faradaic efficiency. -2The voltage for complete hydrolysis is 1.43 V, and it exhibits excellent electrocatalytic water splitting performance at a low voltage of 1.58 V in alkaline media. The synergistic effect of the three metals gives Ag / Cu / Co-L superior performance compared to advanced materials. Compared with the prior art, the preparation method of the present invention is simple and the raw materials are cheap. It meets the requirements of electrocatalysts for water splitting at the molecular level, providing a path for the subsequent design of trimetallic bistriazole-based metal-organic framework electrocatalytic materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a schematic diagram of the crystal structure of the single metal coordination polymer Co-L in Example 3.
[0032] Figure 2 This is the morphology and composition diagram of the trimetallic coordination polymer Ag / Cu / Co-L of Example 7.
[0033] In the figure: (a) shows the SEM image of the trimetallic coordination polymer Ag / Cu / Co-L, (b) shows the TEM image of the trimetallic coordination polymer Ag / Cu / Co-L, and (c) to (f) show the element mapping of the trimetallic coordination polymer Ag / Cu / Co-L.
[0034] Figure 3 It is a schematic diagram comparing the OER and HER electrochemical performances of the single-metal coordination polymers Co-L, Cu-L, Ag-L, the bimetallic coordination polymers Cu / Co-L, Ag / Co-L, and the trimetallic coordination polymer Ag / Cu / Co-L in Examples 1-7.
[0035] In the figure: (a) shows the single metal coordination polymer, the double metal coordination polymer and the trimetallic coordination polymer in 100mL (1 mol∙L -1 ) LSV curves of OER performance test in KOH aqueous solution, (b) shows the LSV curves of single metal coordination polymer, bimetallic coordination polymer and trimetallic coordination polymer in 100 mL (1 mol∙L -1 ) LSV curve of HER performance test in KOH aqueous solution.
[0036] Figure 4 Schematic diagram comparing the electrochemical properties of the trimetallic coordination polymer Ag / Cu / Co-L obtained with different silver metal molar ratios in Example 7.
[0037] In the figure: (a) to (c) show the trimetallic coordination polymers Ag / Cu / Co-L obtained with different silver metal molar ratios in 100mL (1 mol∙L -1) LSV curves, Tafel slopes, and EIS spectra of the OER performance test in KOH aqueous solution. (d) to (f) show the trimetallic coordination polymers Ag / Cu / Co-L obtained with different silver metal molar ratios in 100 mL (1 mol∙L -1 ) LSV curve, Tafel slope diagram and EIS spectrum of HER performance test in KOH aqueous solution.
[0038] Figure 5 Schematic diagram comparing the electrochemical properties of the trimetallic coordination polymer Ag / Cu / Co-L obtained with different silver metal molar ratios in Example 7.
[0039] In the figure: (a) shows RuO2 in 100 mL (1 mol∙L -1 ) LSV curves of the OER performance test in KOH aqueous solution, (b) shows the LSV curves of the trimetallic coordination polymer Ag / Cu / Co-L obtained with different silver metal molar ratios in 100 mL (1 mol∙L -1 ) LSV curve of OER performance test in KOH aqueous solution, (c) O2 volume data of the Ag / Cu / Co-L electrolyzer at the initial, 500 and 1000 cycles, (d) represents the Pt / C in 100 mL (1 mol∙L -1 ) LSV curves of HER performance test in KOH aqueous solution, (e) shows the LSV curves of trimetallic coordination polymers Ag / Cu / Co-L obtained with different silver metal molar ratios in 100 mL (1 mol∙L -1 ) LSV curve of HER performance test in KOH aqueous solution, (f) Volume data of gas H2 produced in Ag / Cu / Co-L electrolyzer at the initial, 500 and 1000 cycles of full hydrolysis.
[0040] Figure 6 This is a schematic diagram of the full hydrolysis electrochemical performance of the trimetallic coordination polymer Ag / Cu / Co-L obtained in Example 7 with different silver metal molar ratios.
[0041] In the figure: (a) shows the trimetallic coordination polymer Ag / Cu / Co-L obtained by RuO2, Pt / C and different silver metal molar ratios in 100 mL (1 mol∙L -1 ) LSV curve of the electrochemical performance test of full hydrolysis in KOH aqueous solution, (b) shows the LSV curve corresponding to the LSV curve at 10 mA∙cm -2 The voltage corresponding to the trimetallic coordination polymers obtained by RuO2, Pt / C and different silver metal molar ratios, (c) Ag / Cu / Co-L in 100 mL (1 mol∙L -1) It curve of electrochemical performance test of full hydrolysis in KOH aqueous solution for 3 h, (d) Ag / Cu / Co-L in 100 mL (1 mol∙L -1 ) LSV curves before and after 3 h full hydrolysis electrochemical performance test in KOH aqueous solution.
[0042] Figure 7 This is the structural diagram of the trimetallic coordination polymer Ag / Cu / Co-L of Example 7. DETAILED DESCRIPTION
[0043] The present invention will be further described below in conjunction with the embodiments.
[0044] Example 1
[0045] To prepare the monometallic coordination polymer Ag-L, 10 mg of the ligand {H2BBTA = 1,5-dihydrobenzo[1,2-d:4,5-d']bis[1,2,3]triazole} and 10.6 mg of silver chloride were added to 2 ml of acetonitrile, 2 ml of N,N-dimethylformamide, and 0.25 ml of hydrochloric acid and stirred evenly for 30 minutes. The mixed solution was then placed in a 25 mL stainless steel autoclave lined with polytetrafluoroethylene and sealed. The autoclave was then placed in a 70°C oven for 72 hours. After slowly cooling to room temperature, the crystals were filtered, washed twice with methanol, and finally dried in a vacuum drying oven at 70°C for 10 hours.
[0046] Example 2
[0047] Preparation of the single-metal coordination polymer Cu-L: 10 mg of the ligand {H2BBTA = 1,5-dihydrobenzo[1,2-d:4,5-d']bis[1,2,3]triazole} and 10.2 mg of copper chloride dihydrate were added to 2 ml of acetonitrile, 2 ml of N,N-dimethylformamide, and 0.25 ml of hydrochloric acid and stirred evenly for 30 minutes. The mixed solution was then placed in a 25 mL stainless steel autoclave lined with polytetrafluoroethylene and sealed. The autoclave was then placed in a 70°C oven for 72 hours. After slowly cooling to room temperature, the crystals were filtered, washed twice with methanol, and finally dried in a vacuum drying oven at 70°C for 10 hours.
[0048] Example 3
[0049] Preparation of single metal coordination polymer Co-L: 10 mg of ligand {H2BBTA = 1,5-dihydrobenzo [1,2-d: 4,5-d'] bis [1,2,3] triazole} and 14.3 mg of cobalt chloride hexahydrate were added to 2 ml of acetonitrile, 2 ml of N, N-dimethylformamide and 0.25 ml of hydrochloric acid, and stirred evenly for 30 minutes. The mixed solution was then placed in a 25 mL stainless steel autoclave lined with polytetrafluoroethylene and sealed. It was then placed in a 70 ° C oven for 72 hours. After slowly cooling to room temperature, the crystals were filtered, washed twice with methanol, and finally dried in a vacuum drying oven at 70 ° C for 10 hours. The schematic diagram of the crystal structure of the single metal coordination polymer Co-L is shown in the figure. Figure 1 shown.
[0050] Example 4
[0051] Preparation of bimetallic coordination polymer Cu / Co-L: 10 mg of ligand {H2BBTA = 1,5-dihydrobenzo[1,2-d:4,5-d']bis[1,2,3]triazole}, 14.3 mg of cobalt chloride hexahydrate, and 10.2 mg of cupric chloride dihydrate were added to 2 ml of acetonitrile, 2 ml of N,N-dimethylformamide, and 0.25 ml of hydrochloric acid and stirred evenly for 30 min. The mixed solution was then placed in a 25 mL stainless steel autoclave lined with polytetrafluoroethylene and sealed. The autoclave was then placed in a 70 °C oven for 72 h, slowly cooled to room temperature, washed twice with methanol, and finally dried in a vacuum drying oven at 70 °C for 10 h.
[0052] Example 5
[0053] Preparation of bimetallic coordination polymer Ag / Co-L: 10 mg of ligand {H2BBTA = 1,5-dihydrobenzo[1,2-d:4,5-d']bis[1,2,3]triazole}, 10.6 mg of silver chloride, and 14.3 mg of cobalt chloride hexahydrate were added to 2 ml of acetonitrile, 2 ml of N,N-dimethylformamide, and 0.25 ml of hydrochloric acid and stirred evenly for 30 min. The mixed solution was then placed in a 25 mL stainless steel autoclave lined with polytetrafluoroethylene and sealed. The mixture was then placed in a 70 °C oven for 72 h, slowly cooled to room temperature, washed twice with methanol, and finally dried in a vacuum drying oven at 70 °C for 10 h.
[0054] Example 6
[0055] Preparation of bimetallic coordination polymer Ag / Cu-L: 10 mg of ligand {H2BBTA = 1,5-dihydrobenzo[1,2-d:4,5-d']bis[1,2,3]triazole}, 10.6 mg of silver chloride, and 10.2 mg of cupric chloride dihydrate were added to 2 ml of acetonitrile, 2 ml of N,N-dimethylformamide, and 0.25 ml of hydrochloric acid and stirred evenly for 30 min. The mixed solution was then placed in a 25 mL stainless steel autoclave with a polytetrafluoroethylene liner and sealed. The mixture was then placed in a 70 °C oven for 72 h, slowly cooled to room temperature, washed twice with methanol, and finally dried in a vacuum drying oven at 70 °C for 10 h.
[0056] Example 7
[0057] To prepare the trimetallic coordination polymer Ag / Cu / Co-L, 10 mg of ligand {H2BBTA = 1,5-dihydrobenzo[1,2-d:4,5-d']bis[1,2,3]triazole}, silver chloride, cobalt chloride hexahydrate, and cupric chloride dihydrate were mixed in a molar ratio of 0.5:1:1, 1:1:1, 1.5:1:1, 2:1:1, 2.5:1:1, and 3:1:1 for Ag / Cu / Co, and added to 2 ml of acetonitrile, 2 ml of N,N-dimethylformamide, and 0.25 ml of hydrochloric acid. The mixture was stirred evenly for 30 min, and then the mixed solution was placed in a 25 mL stainless steel autoclave with a polytetrafluoroethylene liner and sealed, and then stored in an oven at 70 °C for 72 min. h, slowly cooled to room temperature, washed twice with methanol, and finally dried in a vacuum drying oven at 70 ° C for 10 h; the structure of the trimetallic coordination polymer Ag / Cu / Co-L is shown in Figure 7 shown.
[0058] Example 8
[0059] The material morphology and composition of the trimetallic coordination polymer Ag / Cu / Co-L prepared in Example 7 were investigated. Figure 2 The SEM and TEM images show the rod-like structure of Ag / Cu / Co-L, with a thickness of approximately 0.1-0.2 μm. The corresponding elemental mapping (EDS) images confirm the uniform distribution of Ag, Cu, and Co on the Ag / Cu / Co-L nanorods, indicating good dispersion.
[0060] Example 9
[0061] The single-metal coordination polymers, bimetallic coordination polymers, and trimetallic coordination polymers prepared in Examples 1-7 were made into electrodes, and their electrochemical performance in 100 mL (1.0 mol∙L -1) OER electrochemical performance in KOH aqueous solution, it was found that different metal doping has an important influence on OER activity. The polarization curve obtained by LSV test shows that the trimetallic coordination polymer Ag / Cu / Co-L exhibits the highest activity in the OER process, such as Figure 3 At 10 mA∙cm -2 Ag / Cu / Co-L has a low overpotential at a current density of -209 mV (10 mA∙cm -2 vs. RHE), it has a high Faradaic efficiency and exhibits excellent electrocatalytic activity.
[0062] The single-metal coordination polymers, bimetallic coordination polymers, and trimetallic coordination polymers prepared in Examples 1-7 were made into electrodes, and their electrochemical performance in 100 mL (1.0 mol∙L -1 ) HER electrochemical performance in KOH aqueous solution, it was found that different metal doping has an important influence on HER activity. The polarization curve obtained by LSV test shows that Ag / Cu / Co-L exhibits the highest activity in the HER process, such as Figure 3 At 10 mA∙cm -2 Ag / Cu / Co-L has a low overpotential at a current density of 100 mA∙cm. The overpotential of HER in 1 M KOH solution is 208 mV (10 mA∙cm -2 vs. RHE), it has a high Faradaic efficiency and exhibits excellent electrocatalytic activity.
[0063] Example 10
[0064] The trimetallic coordination polymer Ag prepared in Example 7 x / Cu x / Co x -L was prepared into electrodes and the -1 ) in a KOH aqueous solution and found that the amount of Ag doping has an important influence on the OER activity, such as Figure 4 As shown in the figure. The polarization curve obtained by LSV test shows that the current density of Ag1Cu1Co1-L increases almost vertically, indicating that it has the highest OER electrocatalytic activity. In contrast, the bare CP shows very weak OER activity. According to the LSV curve calculation, it is found that Ag1Co1Cu1-L only needs a low overpotential of 208 mV to drive 10 mA∙cm -2 This is much better than other catalysts, even better than the commercial noble metal RuO2 catalyst with an overpotential of 260 mV. -2When the overpotential is 208 mV, the Tafel slope of Ag1Co1Cu1-L is 35.89 mV∙dec -1 , the smallest among all materials, indicating efficient charge transport. Tafel slope data can directly reflect the catalytic kinetics of the electrode material. Notably, the OER performance of Ag1Cu1Co1-L is significantly superior to that of most previously reported pristine MOFs. Electrochemical impedance spectroscopy (EIS), a powerful tool, explains the superior activity of AgCuCo-L. The low charge transfer resistance of Ag1Cu1Co1-L, 0.67 Ω, indicates faster charge transfer and more favorable catalytic kinetics.
[0065] The trimetallic coordination polymer Ag prepared in Example 7 x / Cu x / Co x −L was prepared into an electrode and the -1 ) was used to test the HER performance in a KOH aqueous solution and found that the doping amount of Ag had an important influence on the HER activity, such as Figure 4 As shown in the figure. The polarization curves obtained by LSV test show that Ag1Cu1Co1-L has the highest HER electrocatalytic activity. -2 The overpotential is 209 mV, which is much lower than the overpotential of Pt / C (227 mV) and other materials, showing excellent electrocatalytic activity. -2 When the overpotential is 209 mV, the Tafel slope of Ag1Co1Cu1-L is 61.20 mV∙dec -1 , the smallest among all materials, indicating efficient charge transport. Tafel slope data can directly reflect the catalytic kinetics of the electrode material. Notably, Ag1Cu1Co1-L exhibits far superior HER performance to most previously reported pristine MOFs. Electrochemical impedance spectroscopy (EIS), a powerful tool for HER analysis, explains the superior activity of AgCuCo-L. Ag1Cu1Co1-L exhibits the lowest EIS value and the fastest charge transfer rate.
[0066] Example 11
[0067] RuO2 and the trimetallic coordination polymer Ag prepared in Example 7 x / Cu x / Co x −L was made into an electrode and in 100 mL (1 mol∙L -1 ) was used to test the OER performance in a KOH aqueous solution and found that the doping amount of Ag had an important influence on the OER activity, such as Figure 5 At 10 mA∙cm -2 When RuO2 and Ag x / Cu x / Co x The −L electrolyzer exhibited excellent durability during the OER process initially, and after 500 and 1000 cycles, indicating its good stability.
[0068] Pt / C and the trimetallic coordination polymer Ag prepared in Example 7 x / Cu x / Co x −L was made into an electrode and in 100 mL (1 mol∙L -1 ) was used to test the HER performance in a KOH aqueous solution and found that the doping amount of Ag had an important influence on the HER activity, such as Figure 5 At 10 mA∙cm -2 When Pt / C and Ag x / Cu x / Co x The −L electrolyzer exhibited excellent durability during the OER process initially, and after 500 and 1000 cycles, indicating its good stability.
[0069] Example 12
[0070] Due to its excellent OER and HER performance, Ag1Cu1Co1-L electrode has been further used as anode and cathode for overall water splitting, such as Figure 6 Ag1Cu1Co1-L exhibited excellent catalytic activity at a current density of 10 mA∙cm -2 Under these conditions, the overall hydrolysis voltage was 1.58 V. Furthermore, the Ag1Cu1Co1-L electrolytic cell demonstrated excellent durability over a 3-h overall hydrolysis period, as shown in its IT and LSV spectra, indicating good stability. The amounts of hydrogen and oxygen produced by the Ag1Cu1Co1-L electrocatalyst were measured using an H-type electrolytic cell separated by a Nafion membrane (water discharge method). The AgCuCo-L electrocatalyst exhibited high Faradaic efficiency throughout the test.
Claims
1. A method for preparing a coordination polymer-based electrocatalyst, characterized in that: L is the organic ligand, and Cu in the transition metal salt TM 2+ 、Co 2+ and Ag + As nodes, single metal coordination polymers Co-L, Cu-L, Ag-L, bimetallic coordination polymers Cu / Co-L, Ag / Co-L, Ag / Cu-L and trimetallic coordination polymers Ag / Cu / Co-L were prepared by a hydrothermal method. The synthesis routes are as follows: For monometallic: L+TM→Co-L or L+TM→Cu-L or L+TM→Ag-L; For bimetallic: L+TM→Cu / Co-L, L+TM→Ag / Co-L, L+TM→Ag / Cu-L; For tri-metals: L+TM→Ag / Cu / Co-L; The organic ligand L is selected from {H2BBTA=1,5-dihydrobenzo[1,2-d:4,5-d']bis[1,2,3]triazole}, The molecular formula is C6H4N6, and has the following (A) molecular structure: ; The transition metal salt TM is selected from silver chloride, cobalt chloride hexahydrate or cupric chloride dihydrate; The preparation method includes the preparation of single metal coordination polymers Co-L, Cu-L, Ag-L, the preparation of double metal coordination polymers Cu / Co-L, Ag / Co-L, Ag / Cu-L and the preparation of trimetallic coordination polymer Ag / Cu / Co-L: (1) The preparation of single metal coordination polymers Co-L, Cu-L, and Ag-L comprises the following steps: Step 1, add 8-10 mg of ligand {H2BBTA=1,5-dihydrobenzo[1,2-d:4,5-d']bis[1,2,3]triazole}, 9-12 mg of silver chloride, 13-16 mg of cobalt chloride hexahydrate or 10-13 mg of cupric chloride dihydrate to 1-3 ml of acetonitrile, 1-3 ml of N,N-dimethylformamide and 0.25-0.5 ml of hydrochloric acid, and stir evenly for 25-35 min; Step 2, adding the mixed solution prepared in step 1 into a 25-50 mL stainless steel autoclave lined with polytetrafluoroethylene and sealing it, then storing it in an oven at 30-70°C for 48-72 hours, slowly cooling it to room temperature, filtering the crystals, washing them with methanol 1-3 times, and finally drying them in a vacuum drying oven at a temperature of 60-80°C for a time of 6-12 hours; (2) Preparation of bimetallic coordination polymers Cu / Co-L, Ag / Co-L, and Ag / Cu-L, comprising the following steps: Step 1, add 8-10 mg of ligand {H2BBTA=1,5-dihydrobenzo[1,2-d:4,5-d']bis[1,2,3]triazole}, 9-12 mg of silver chloride, 13-16 mg of cobalt chloride hexahydrate and 10-13 mg of cupric chloride dihydrate in a molar ratio of Co / Cu, Ag / Co and Ag / Cu of 1:1, to 1-3 ml of acetonitrile, 1-3 ml of N,N-dimethylformamide and 0.25-0.5 ml of hydrochloric acid, and stir evenly for 25-35 min; Step 2, placing the mixed solution obtained in step 1 into a 25-50 mL stainless steel autoclave with a polytetrafluoroethylene liner and sealing it, then storing it in an oven at 30-70°C for 48-72 hours, slowly cooling it to room temperature, washing it with methanol 1-3 times, and finally drying it in a vacuum drying oven at a temperature of 60-80°C for a time of 6-12 hours; (3) Preparation of trimetallic coordination polymer Ag / Cu / Co−L, comprising the following steps: Step 1, add 8-10 mg of ligand {H2BBTA=1,5-dihydrobenzo[1,2-d:4,5-d']bis[1,2,3]triazole}, 9-12 mg of silver chloride, 13-16 mg of cobalt chloride hexahydrate and 10-13 mg of cupric chloride dihydrate in a molar ratio of Ag / Cu / Co (0.5-3):1:1 to 1-3 ml of acetonitrile, 1-3 ml of N,N-dimethylformamide and 0.25-5 ml of hydrochloric acid, and stir evenly for 25-35 min; Step 2: Place the mixed solution obtained in step 1 into a 25-50 mL stainless steel autoclave with a polytetrafluoroethylene liner and seal it, then place it in an oven at 30-70 ° C for 48-72 h, slowly cool it to room temperature, wash it with methanol 1-3 times, and finally dry it in a vacuum drying oven at a temperature of 60-80 ° C for 6-12 h.
2. Use of the coordination polymer-based electrocatalyst prepared according to the method of claim 1 in electrocatalytic water decomposition.
Citation Information
Cited By
Preparation method and application of oxygen reduction electrocatalyst based on natural polyphenol
CN122051257A